A randomized, crossover pharmacokinetic study comparing generic tacrolimus vs. the reference formulation in subpopulations of kidney transplant patients. (11th October 2013) - Bloom, R. D.; Trofe‐Clark, J.; Wiland, A.; Alloway, R. R.
Abstract An exploratory, post hoc analysis was performed using data from a prospective, multicenter, open‐label, randomized, two‐period (14 d per period), two‐sequence, crossover, steady‐state pharmacokinetic study comparing generic tacrolimus (Sandoz) vs. reference tacrolimus in stable renal transplant patients receiving their pre‐study twice‐daily dose. Pharmacokinetic parameters were compared in 68 patients according to gender, African American ethnicity, the presence or absence of diabetes, and use of steroids. The ratios of tacrolimus AUC0–12 h, Cmax, and C12 with generic vs. reference tacrolimus were calculated using the geometric mean (GM) of dose‐normalized values at days 14 and 28. Mean (SD) tacrolimus dose at baseline was 5.7 (4.2) mg/d. There were no consistent differences in dose‐normalized AUC0–12 h, C12, Cmax, or tmax between the generic and reference preparations within subpopulations. The 90% confidence intervals (CI) for the ratios of dose‐normalized AUC0–12 h and C12 with generic vs. reference tacrolimus were within 80–125% for all subpopulations, as were 90% CIs for Cmax other than for females, African Americans, and non‐diabetics, which is not unexpected given the wide variability of tacrolimus Cmax and the small subpopulation sizes. These exploratory results suggest that this generic tacrolimus preparation would be expected to offer comparable bioavailability to the reference drug in these patient subpopulations.